Age Discrimination at Workplace: A Study of Service Sector Organizations in Nepal - Sapkota, Durga; Bhattarai, Bishnu Prasad (Journal of Business and Management, 2025)
Background: Workplace age discrimination has been recognized globally as a significant issue, leading to negative outcomes for employees, employers, and their relationships. While management practices and positive organizational cultures can mitigate ageism, it remains an under-researched area in Nepal. Unlike gender or caste-based discrimination, ageism in Nepalese workplaces is rarely acknowledged, with limited understanding of its prevalence, forms, and impacts. Objectives: The primary purpose of this study is to determine the relationship between selected factors (inter-generational contact, worker bias, job-age stereotypes and attitude towards elderly) and age discrimination in Nepalese service sector organization context. Methods: The study uses a quantitative approach with descriptive, correlational, and causal-comparative methods to analyze factors influencing age discrimination in Nepal’s service sector. Convenience sampling was used to collect 200 samples from service sector organizations within Kathmandu valley. Structured questionnaires were used to collect study data. The data collection period was September to November 2024. Results: The regression analysis revealed an R² value of 0.267, indicating that 26.7% of variation in age discrimination is explained by the independent variables taken in the study. The model’s statistical significance (p < 0.01) confirms that at least one beta coefficient is non-zero. Additionally, Variance Inflation Factor (VIF) values for all independent variables are below 2, confirming the absence of multicollinearity and validating the suitability of these variables for regression analysis. Conclusion: The result of the study revealed that worker bias and job-age stereotypes have significant influence on age discrimination. Therefore, organizations have to provide more emphasis on these two variables in order to reduce age discrimination problems. JEL Classification: C93, C9, J14, J1